Genome evolution of the psammophyte Pugionium for desert adaptation and further speciation - Hu, Quanjun; Ma, Yazhen; Mandáková, Terezie; Shi, Sheng; Chen, Chunlin; Sun, Pengchuan; Zhang, Lei; Feng, Landi; Zheng, Yudan; Feng, Xiaoqin; Yang, Wenjie; Jiang, Jiebei; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2021)
Deserts exert strong selection pressures on plants, but the underlying genomic drivers of ecological adaptation and subsequent speciation remain largely unknown. Here, we generated de novo genome assemblies and conducted population genomic analyses of the psammophytic genus Pugionium (Brassicaceae). Our results indicated that this bispecific genus had undergone an allopolyploid event, and the two parental genomes were derived from two ancestral lineages with different chromosome numbers and structures. The postpolyploid expansion of gene families related to abiotic stress responses and lignin biosynthesis facilitated environmental adaptations of the genus to desert habitats. Population genomic analyses of both species further revealed their recent divergence with continuous gene flow, and the most divergent regions were found to be centered on three highly structurally reshuffled chromosomes. Genes under selection in these regions, which were mainly located in one of the two subgenomes, contributed greatly to the interspecific divergence in microhabitat adaptation.
Keywords: microhabitat divergence; vznik druhů (genetika); Polyploidy; genom rostlinný; desert plants; polyploidization; chromosomal structural variation; Genome, Plant; ekosystém; Ecosystem; fylogeneze; fyziologická adaptace; Phylogeny; Genetic Speciation; Brassicaceae; polyploidie; Adaptation, Physiological